IMPLEMENTASI SISTIM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI PROYEK KONSTRUKSI GEDUNG OLEH PELAKSANA JASA KONSTRUKSI DI KOTA SOLOK TAHUN 2021 - Reri Risnaldi; Masril Masril; Helga Yermadona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: In construction projects, it is hoped that there will be zero accidents, this can be implemented properly if 6 (six) key elements for the successful implementation of the Occupational Safety and Health Management System (K3), namely K3 policy, planning, implementation and operation, inspection and corrective action , management review and continuous improvement, well executed. This research is a quantitative research using descriptive analysis. Data was collected using a questionnaire in the form of interviews and field observations. The research was conducted in the Solok City building project. The results of research on construction projects by Construction Service Executors in Solok City (60.00%). Of the three parameters, namely knowledge, ability and willingness, the good parameters are only knowledge (57%), ability parameters (53.5%) and willingness parameters (56.7%). From the results of the research, it is suggested that every construction service provider must carry out their duties and authorities as stated in PermenPU Number 5/PRT/M/2014 concerning Guidelines for the Occupational Safety and Health Management System (SMK3) for Construction in the Public Works Sector.Keywords: Knowledge, Ability and Willingness of Implementation of SMK3, Implementing Construction Services.